Two or Three on the Bed?: Jerome’s Interpretation of Isaiah 28:20 Reflecting Jewish Traditions - Kato, Teppei (Vulgata in dialogue, 2024)
A given translation of the Bible may appear mistranslated because it privileges a particular interpretation. This feature of exegetical particularity makes it extremely difficult to identify mistranslations of the Bible. For example, two versions in the Latin translation of Isa 28:20 inform Jerome’s apparent mistranslation: one with two people sleeping on the bed and the other with three. This example may appear a “mistranslation” by Jerome. However, through this translation, we can glimpse the Jewish tradition that informs its reading.